Climate, Induced Migration and Farmer, Herder Conflicts: The Mediating Role of Border Delineation in the Nigeria, Cameroon Bakassi Peninsula Fallout (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This paper examines the intricate nexus between climate, induced environmental stress, human migration, and violent conflict, with a specific focus on the mediating and exacerbating role of international border delineation. Using the protracted dispute over the Bakassi Peninsula between Nigeria and Cameroon as a critical case study, it argues that climate change acts as a threat multiplier in a historically contested border region, transforming environmental scarcity into geopolitical and inter, communal tension. The analysis traces how rising sea levels, coastal erosion, and freshwater salinization in the Gulf of Guinea have degraded livelihoods, forcing communities, primarily Nigerian fishers and farmers, to migrate inward. This movement intersects with pre, existing patterns of herder migration from Nigeria’s arid north, also intensified by climate pressures, leading to heightened competition over arable land and resources in Nigeria’s border states. The paper posits that the ambiguous and contested nature of the Nigeria, Cameroon border, culminating in the 2002 International Court of Justice (ICJ) ruling ceding Bakassi to Cameroon, created a unique zone of legal uncertainty, weak governance, and militarization. This environment mediated the translation of climate, induced migration into violent farmer, herder conflicts. The border delineation did not merely provide a backdrop but actively shaped the pathways of displacement, the contestation of citizenship and land rights, and the efficacy of state responses. Through an interdisciplinary lens combining political geography, environmental security, and conflict studies, this paper concludes that effective conflict resolution in the region must simultaneously address the twin challenges of climate resilience and post, adjudication borderland integration, moving beyond purely legalistic solutions to incorporate human security and ecological sustainability.